The Clinical Impact of 16S Ribosomal RNA Polymerase Chain Reaction Bacterial Sequencing in Infectious Endocarditis: A Single Center Experience. Issue 3 (May 2020) - El-Dalati, Sami; Riddell, James; Fagan, Christopher; Owczarczyk, Anna B.; Fukuhara, Shinichi; Wasylyshyn, Anastasia; Patel, Twisha; Cinti, Sandro
Abstract : Introduction: Cases of possible and/or culture-negative endocarditis continue to be a diagnostic challenge. Performing bacterial 16S ribosomal RNA polymerase chain reaction (16S rRNA PCR) sequencing on cardiac valves allows providers to acquire microbiologic information that was previously unobtainable. However, few publications address how the polymerase chain reaction (PCR) results impact clinical management in endocarditis patients. Methods: Between July 1, 2014, and December 31, 2018, we reviewed the results of all 16S rRNA PCR bacterial sequencing tests collected from cardiac valves at the University of Michigan. Each patient's chart was then evaluated by 2 independent infectious diseases physicians to determine whether the medical plans were impacted by the results. Results: Forty-one patients were identified with associated 16S rRNA PCR testing from 165 explanted cardiac valves. Eighteen samples (43.9%) were positive, and 5 (12.2%) of 41 patients had their management plans changed based on the PCR findings. In 23 (56.1%) of 41 cases, the PCR result was never referenced by any medical provider in the electronic medical record. There were 7 cases (17.1%) where patients received 6 weeks of antibiotics despite presenting with possible culture-negative endocarditis, noninfectious operative findings, and negative valve PCRs, which were not reviewed. Conclusions: 16S rRNA PCR sequencing is a useful tool for obtaining a microbiologic diagnosis in cases of possible or culture-negative endocarditis. The test has potential to impact patient care and in a subset of cases could be used to deescalate antibiotic therapy. However, testing delays and cumbersome resulting methods impede bacterial sequencing from reaching its full potential as a diagnostic modality. Abstract : Performing bacterial 16S ribosomal RNA polymerase chain reaction sequencing on cardiac valves allows providers to acquire microbiologic information that was previously unobtainable. It can be a useful tool for obtaining a microbiologic diagnosis in cases of possible or culture-negative endocarditis. Additionally, the test has the potential to impact patient care, and in a subset of cases could be used to de-escalate antibiotic therapy.